Behavior of Corrosion of a Heat Pipe Cooling Device in a Computer - Rittidech, S.; Rodbumrung, A. (Engineering, Technology & Applied Science Research, 2017)
The aim of this study was to perform life testing and to determine the effect of working time on the corrosion of a heat pipe used for cooling in a computer. The heat pipe was made from a copper tube. The heat pipe consists of evaporator and condenser section. It had a specification similar with the use in ordinary computers, the working fluid being distilled water. When the computer starts, the concentration of the copper solution slightly increases. The greater copper concentration was 0.00062 ppm upon 3000-5000 hours of testing. The surface traces of corrosion rises due to the oxidation of the porous material within the working fluid. The test found that oxygen (O) and carbon (C) are component contents.